Bioinorganic medicinal chemistry - Alessio, E. (Enzo) (Weinheim : Wiley-VCH ; Chichester : John Wiley [distributor], 2011)
This book gives a comprehensive overview about medicinal inorganic chemistry. Topics like targeting strategies, mechanism of action, Pt-based antitumor drugs, radiopharmaceuticals are covered in detail and offer the reader an in-depth overview about this important topic.
Front Matter -- Medicinal Inorganic Chemistry: State of the Art, New Trends, and a Vision of the Future / Nicola J Farrer, Peter J Sadler -- Targeting Strategies for Metal-Based Therapeutics / Julia F Norman, Trevor W Hambley -- Current Status and Mechanism of Action of Platinum-Based Anticancer Drugs / Shanta Dhar, Stephen J Lippard -- New Trends and Future Developments of Platinum-Based Antitumor Drugs / Xiaoyong Wang, Zijian Guo -- Ruthenium and Other Non-Platinum Anticancer Compounds / Ioannis Bratsos, Teresa Gianferrara, Enzo Alessio, Christian G Hartinger, Michael A Jakupec, Bernhard K Keppler -- The Challenge of Establishing Reliable Screening Tests for Selecting Anticancer Metal Compounds / Angela Boccarelli, Alessandra Pannunzio, Mauro Coluccia -- Gold-Based Therapeutic Agents: A New Perspective / Susan J Berners-Price -- MRI Contrast Agents: State of the Art and New Trends / Daniela Delli Castelli, Eliana Gianolio, Silvio Aime -- Metal-Based Radiopharmaceuticals / Roger Alberto -- Boron and Gadolinium in the Neutron Capture Therapy of Cancer / Ellen L Crossley, H Y Vincent Ching, Joseph A Ioppolo, Louis M Rendina -- Essential Metal Related Metabolic Disorders / Yasmin Mawani, Chris Orvig -- Metal Compounds as Enzyme Inhibitors / Gilles Gasser, Nils Metzler-Nolte -- Biomedical Applications of Metal-Containing Luminophores / Albert Ruggi, David N Reinhoudt, Aldrik H Velders -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Pharmaceutical chemistry; Inorganic compounds -- Therapeutic use; MEDICAL -- Pharmacology; Electronic books